Implementation of an Accounting Information System at a Grocery Store - Jaya, Wiliam Prayoga; Harnadi, Bernardinus; Chrismastuti, Agnes Advensia (Soegijapranata Catholic University, 2025)
In the digital era, both companies and MSMEs are starting to utilize technology to help their work. Grocery Store is store that sells various kinds of goods such as basic necessities, drinks, snacks, and daily necessities. This shop has many customers but the recording procedure is done manually. This research aims to help Grocery Stores by creating an accounting information system using the RAD (Rapid Application Development) method. This method was chosen in reason the effectiveness in developing and organizing the system structure. This accounting information system can help the store in managing transaction and inventory data better.